(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Filters occupy important acts in several Radio Frequency microwave applications. Several applications such as wireless communications still challenge RF/microwave filters with strict requirements such as smaller size, higher performance, lighter weight, and lower cost. Microstrip Filters for RF/Microwave Applications offers a unique and comprehensive treatment of RF/microwave filters based on the microstrip structure. One of the most common methods in designing microwave filters is using of parallel-coupled microstrip. In this paperÂ simulate and fabricate by using Ansoft Designer a two resonator microstrip band-pass filter suitable for Wi-Fi applications.Â The results of simulation were quite good.